Cardiac surgery for Chagas disease. Issue 10 (14th September 2018) - Magarakis, Michael; Macias, Alejandro E.; Tompkins, Bryon A.; Reis, Victor; Loebe, Matthias; Batista, Randas; Salerno, Tomas A.
Abstract: Although Chagas disease is a rare entity in North America, it is associated with significant cardiac morbidity. It is estimated that 20‐30% of those who are infected will eventually develop cardiovascular disease secondary to Chagas disease. We review the literature and share our experience on the surgical management of this challenging patient population.